Public Health Significance of Major Bacterial Zoonotic Diseases: A One Health Perspective - , Mautusi Chakraborty; , J B Rajesh; , Jashima Debbarma; , C Christen; , Payel Kar; , Manas Das; , Binipi Debbarma; , Loukrakpam Khwaisana; , Lalhmingmawii Sailo; Rahul, (Archives of Current Research International, 2025)
Bacterial zoonotic diseases lead to a serious threat to global public health, particularly in low- and middle-income countries where close human-animal interactions and insufficient surveillance systems increase the risk of transmission. This review describes the five-key bacterial zoonotic diseases like brucellosis, leptospirosis, tuberculosis, salmonellosis, and listeriosis. It is explaining mainly their causes, transmission pathways, clinical features, diagnostic methods, treatments, and control measures. These infections not only endanger human and animal health but also cause huge economic loss, especially in livestock-reliant communities. Disease emergence can be affected by factors such as population growth, human behavior, technological advances, industrial activities, economic development, global travel and trade and microbial evolution. Climate change and environmental destruction are also common factors to the spread and persistence of these infections. The review also shows the importance of the One Health approach, mostly about the collaboration between human and animal health sectors to manage and control these diseases. It deliberates the new diagnostic tools, the growing issue of antibiotic resistance, and gives some examples of successful control programs. Improvement of proper disease monitoring, public education, hygiene practices, and vaccination are essential to reduce the burden of these diseases. Continued research, coming up with new ideas and cooperation among veterinary and medical sectors can greatly reduce the impact of bacterial zoonotic diseases worldwide.